2015
DOI: 10.1093/nar/gkv709
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal position shift of a regulatory gene alters the bacterial phenotype

Abstract: Recent studies strongly suggest that in bacterial cells the order of genes along the chromosomal origin-to-terminus axis is determinative for regulation of the growth phase-dependent gene expression. The prediction from this observation is that positional displacement of pleiotropic genes will affect the genetic regulation and hence, the cellular phenotype. To test this prediction we inserted the origin-proximal dusB-fis operon encoding the global regulator FIS in the vicinity of replication terminus on both a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
3
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 57 publications
5
51
0
Order By: Relevance
“…Consistently, translocation of the fis gene to Ter‐MD sustains the overall expression level of Fis relative to wild type, but causes moderate changes in the expression levels of some genes regulated by Fis, as well as an increase in sensitivity of cells to oxidative stresses and drugs (Gerganova et al . ). Chromosomal locations of some DNA elements can, therefore, be important to strictly exert their regulatory functions.…”
Section: Discussionmentioning
confidence: 97%
“…Consistently, translocation of the fis gene to Ter‐MD sustains the overall expression level of Fis relative to wild type, but causes moderate changes in the expression levels of some genes regulated by Fis, as well as an increase in sensitivity of cells to oxidative stresses and drugs (Gerganova et al . ). Chromosomal locations of some DNA elements can, therefore, be important to strictly exert their regulatory functions.…”
Section: Discussionmentioning
confidence: 97%
“…Another DNA binding protein, the leucine-responsive regulatory protein, Lrp, contributes by stimulating transcription of P ilvIH (Wang et al 1993) A gene may not have to leave its original host cell to experience new patterns of DNA topological influence. Simply repositioning the gene on the single, circular chromosome of the bacterium may achieve this effect (Brambilla and Sclavi 2015;Fitzgerald et al 2015;Gerganova et al 2015). Bioinformatic analyses and experimental work have indicated that gene location can affect expression for reasons other than gene dosage (i.e.…”
Section: Dna Supercoiling Bacterial Evolution and Pathogenesismentioning
confidence: 99%
“…Furthermore, the ribosomal RNAs showing this methylation pattern were localized near the origin of replication. Genomic position does effect expression levels (Gerganova et al , 2015; Muskhelishvili & Travers, 2013).…”
Section: Discussionmentioning
confidence: 99%